Phase-change-mediated transport and agglomeration of fungal spores on wheat awns. Issue 190 (18th May 2022) - Iliff, Grady J.; Mukherjee, Ranit; Gruszewski, Hope A.; Schmale III, David G.; Jung, Sunghwan; Boreyko, Jonathan B.
Abstract : Wheat and other staple crops are devastated by fungal diseases. Many fungal plant pathogens are spread via active or passive discharge of microscopic spores. Here, we described the unique transport of spores of the fungal pathogen Epicoccum tritici, causal agent of black sooty mould, on wheat awns. The unique multi-scale architecture of wheat awns, coupled with condensation and evaporation of dew droplets, facilitated the transport and agglomeration of spores of the fungus. First, dew droplets spontaneously transported spores from the tips of awn hairs to the neighbouring stomatal ridges, driven by gradients in Laplace pressure and surface wettability. Subsequently, spores agglomerated into dry clusters due to the Cheerios effect and evaporation, increasing the likelihood of passive spore removal via wind shear and/or rainsplash. Future plant breeding approaches should consider the development of modified spike structures, such as those without awns or awn hairs, to reduce the potential for spread of fungal plant pathogens.